2020
DOI: 10.13057/biodiv/d210625
|View full text |Cite
|
Sign up to set email alerts
|

Identification of compounds isolated from a methanolic extract of Acanthus ilicifolius leaves and evaluation of their antifungal and antioxidant activity

Abstract: Abstract. Andriani D, Revianti S, Prananingrum W. 2020. Identification of compounds isolated from a methanolic extract of Acanthus ilicifolius leaves and evaluation of their antifungal and antioxidant activity. Biodiversitas 21: 2521-2525. Acanthus ilicifolius L. (Acanthaceae) is commonly found in mangroves along the east coast of Surabaya. It can be used as an indicator of environmental pollution and damage in mangrove ecosystems. Studies have reported that A. ilicifolius has antimicrobial, antifungal, antivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…The methanol extract of A. ilicifolius leaves collected from Wonorejo, East Java, Indonesia, reported alkaloid components, flavonoids, glycosides, polyphenols, steroids, and tannins. In addition, it also reported an IC 50 value of 17.51 µg/ ml of the methanol extract of A. ilicifolius leaves, with a DPPH concentration of 0.06 mM (Andriani et al, 2020).…”
Section: Antioxidant Activity and Total Phenol Content Of The Jeruju ...mentioning
confidence: 88%
“…The methanol extract of A. ilicifolius leaves collected from Wonorejo, East Java, Indonesia, reported alkaloid components, flavonoids, glycosides, polyphenols, steroids, and tannins. In addition, it also reported an IC 50 value of 17.51 µg/ ml of the methanol extract of A. ilicifolius leaves, with a DPPH concentration of 0.06 mM (Andriani et al, 2020).…”
Section: Antioxidant Activity and Total Phenol Content Of The Jeruju ...mentioning
confidence: 88%
“…Sodium benzoate does not cause negative effects when used in small amounts. The level of use of sodium benzoate ranges from 0.05-0.1% [15].…”
Section: Complete Test Resultmentioning
confidence: 99%
“…It is already known that Acanthus ilicifolius extract has antifungal and antioxidant in-vitro and became antifungal to mice that suffered from oral candidiasis 19,23,24 . This study confirmed that the immerse time in effervescent Acanthus ilicifolius extract 4% (Fig.…”
Section: Discussionmentioning
confidence: 99%